Thermal modelling of gallium nitride-based transistor device on diamond substrate - Soh, Ming Wee (Nanyang Technological University, 2023)
Gallium nitride high electron mobility transistors (GaN HEMTs) have gained popularity in recent years in power electronic applications due to their higher power density, faster switching speeds, high operating temperatures, and improved efficiency as compared to traditional silicon (Si)-based transistors. However, limitations of GaN HEMT still exist including the higher cost of manufacturing, more prone to gate oxide breakdowns, non-compatible with existing manufacturing processes, and thermal management. Diamond offers exceptional properties such as high thermal conductivity, high mechanical strength, and high electrical resistivity. This project aims to study the effects of various parameters of diamond as the substrate for GaN HEMT. DC characteristics and the global device temperatures have been obtained for GaN HEMT on different substrates such as diamond, Si, and silicon carbide (SiC). Using the substrate of diamond, the peak drain current of 773 mA/mm at a drain voltage of 4 V was obtained, and the drain current at a voltage of 20 V was measured at 617 mA/mm. With the self-heating effect, the percentage drop in drain current was 20.18%, the lowest compared to Si of 41.72% and SiC of 28.73%. The peak device temperature was observed to be the lowest for the diamond at 398 K, followed by SiC of 413 K and Si of 459 K at drain voltage=20 V. The thermal conductivity of diamond was varied between 12 WcmK-1, 12.94 WcmK-1, 15 WcmK-1, and 17 WcmK-1. The findings indicate that an increase in thermal conductivity resulted in a reduction of temperature within the device. Moreover, the percentage drop in drain current was observed to decrease accordingly.